Cover Feature: Bidentate Disilicate Framework for Bis‐Grafted Surface Species (Chem. Eur. J. 47/2021). Issue 47 (30th July 2021) - Ishizaka, Yusuke; Arai, Natsumi; Matsumoto, Kazuhiro; Nagashima, Hiroki; Takeuchi, Katsuhiko; Fukaya, Norihisa; Yasuda, Hiroyuki; Sato, Kazuhiko; Choi, Jun‐Chul
Abstract : Synthesizing the "wanted" bald eagle killer : Aetokthonotoxin (AETX), a pentabrominated 1, 2'‐biindole alkaloid has been indicted to elicit vacuolar myelinopathy, a neurologic disease causing the death of birds of prey, such as the bald eagle in the USA. In order to assess further biological activity studies, synthesis of this neurotoxin is decidedly needed. Here, we describe its first total synthesis: by fusing advanced indole intermediates in a Somei‐type Michael reaction in only five steps overall. More information can be found in the Full Paper by M. G. Ricardo, B. Westermann, et al. (DOI: 10.1002/chem.202101848 ).